2022
DOI: 10.3389/fonc.2021.821838
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Optical Imaging-Monitored Synergistic Effect of Radio-Frequency Hyperthermia and Oncolytic Immunotherapy

Abstract: PurposeTo develop a new interventional oncology technique using indocyanine green (ICG)-based interventional optical imaging (OI) to monitor the synergistic effect of radiofrequency hyperthermia (RFH)-enhanced oncolytic immunotherapy.Materials and MethodsThis study included (1) optimization of ICG dose and detection time-window for intracellular uptake by VX2 tumor cells; (2) in-vitro confirmation of capability of using ICG-based OI to assess efficacy of RFH-enhanced oncolytic therapy (LTX-401) for VX2 cells; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…20 21 Previous studies have demonstrated that radiofrequency hyperthermia (RFH) at approximately 42°C can significantly enhance the effect of chemotherapy or oncolytic immunotherapy (such as LTX-401) effect on a variety of malignancies. [22][23][24][25] The potential mechanisms may include (1) RFH-induced modulation of the tumor immune microenvironment via heat shock proteins and subsequent activation of immune systems 26 ; (2) tissue fracturing by heating, increased permeability of the cytoplasmic membrane, deactivation of multidrug resistance pumps, and amplification of cellular metabolism, which facilitate the entrance of therapeutics into the targeted tumor cells. 27 In the present study, LTX-315 was used to kill HCC cells, and subsequently recruit and activate T cells for immunotherapy.…”
Section: Open Accessmentioning
confidence: 99%
“…20 21 Previous studies have demonstrated that radiofrequency hyperthermia (RFH) at approximately 42°C can significantly enhance the effect of chemotherapy or oncolytic immunotherapy (such as LTX-401) effect on a variety of malignancies. [22][23][24][25] The potential mechanisms may include (1) RFH-induced modulation of the tumor immune microenvironment via heat shock proteins and subsequent activation of immune systems 26 ; (2) tissue fracturing by heating, increased permeability of the cytoplasmic membrane, deactivation of multidrug resistance pumps, and amplification of cellular metabolism, which facilitate the entrance of therapeutics into the targeted tumor cells. 27 In the present study, LTX-315 was used to kill HCC cells, and subsequently recruit and activate T cells for immunotherapy.…”
Section: Open Accessmentioning
confidence: 99%